2017
DOI: 10.1038/srep44398
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix and α5β1 integrin signaling control the maintenance of bone formation capacity by human adipose-derived stromal cells

Abstract: Stromal vascular fraction (SVF) cells of human adipose tissue have the capacity to generate osteogenic grafts with intrinsic vasculogenic properties. However, adipose-derived stromal/stem cells (ASC), even after minimal monolayer expansion, display poor osteogenic capacity in vivo. We investigated whether ASC bone-forming capacity may be maintained by culture within a self-produced extracellular matrix (ECM) that recapitulates the native environment. SVF cells expanded without passaging up to 28 days (Unpass-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
(63 reference statements)
0
30
0
Order By: Relevance
“…2e). Integrin signaling pathway plays a critical role in homing of MSCs to the bone, osteogenic differentiation, and bone formation, and even some integrins are suggested as targets to promote bone formation and repair [85][86][87]. Several integrin genes were identified in our data with highly variable expression across the cells, such as ITGA5 and ITGB1, which respectively encode α5 and β1 and together form the α5β1 integrin, a cell surface receptor for fibronectin implicated in the control of osteoblastogenesis [87,88].…”
Section: Discussionmentioning
confidence: 81%
“…2e). Integrin signaling pathway plays a critical role in homing of MSCs to the bone, osteogenic differentiation, and bone formation, and even some integrins are suggested as targets to promote bone formation and repair [85][86][87]. Several integrin genes were identified in our data with highly variable expression across the cells, such as ITGA5 and ITGB1, which respectively encode α5 and β1 and together form the α5β1 integrin, a cell surface receptor for fibronectin implicated in the control of osteoblastogenesis [87,88].…”
Section: Discussionmentioning
confidence: 81%
“…In terms of therapeutic potential, these genes are associated with functional characteristics of MSCs, such as integrin signaling pathway, angiogenesis, and inflammation mediated by chemokine and cytokine signaling pathway (Figure 2E). Integrin signaling pathway plays a critical role in homing of MSCs to bone, osteogenic differentiation, and bone formation, and even some integrins are suggested as targets to promote bone formation and repair (Di Maggio et al, 2017; Marie, 2013; Olivares-Navarrete et al, 2015). Several integrin genes were identified in our data with highly variable expression across the cells, such as ITGA5 and ITGB1 , which respectively encode α5 and β1 and together form the α5β1 integrin, a cell-surface receptor for fibronectin implicated in the control of osteoblastogenesis (Marie, 2013; Park et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have aimed to manipulate ECMmicroenvironment for tissue regeneration by using either artificial ECM or self-produced ECM as a scaffold in the stem cell therapy (Gobaa et al 2011;Martino et al 2014;Takewaki et al 2017;Di Maggio et al 2017;Zhu et al 2017). These studies have demonstrated strikingly improved regenerative efficiency and proposed promising approaches in clinical applications.…”
Section: Resultsmentioning
confidence: 99%